The Shackles of Space and City in the Short Story Iblis Paris by Triyanto Triwikromo - Hapsari, Retno Tyas; Maylani, Isna; Putri, Lintang Nurlissya (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This research aims to explain the construction of urban space more specifically from a postcolonial perspective while also uncovering the power relations that limit subjects within that space. The method used is qualitative with a deconstructive approach to examine colonized discourses that demonstrate colonial and postcolonial domination and hierarchy. Data collection techniques include identifying, classifying, and selectively quoting, considering their relevance to the research problem formulation to support the interpretation of the descriptive and analytical texts. The results show that urban space in the short story is presented not merely as a setting but as a medium for the search for freedom in an effort to find an ideal space.